Hodnocení efektivnosti investičního projektu při respektování ekonomického rizika - Jiráský, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Diplomová práce je zaměřena na hodnocení efektivnosti investičního projektu při respektování ekonomického rizika. Principem pro zpracování práce je charakteristika investičního projektu, analyzování a hodnocení efektivnosti projektu, posouzení ekonomického rizika. Cílem a zároveň výstupem je aplikování těchto zásad pro vypracování na případové studii.

This master’s thesis is aimed to evaluate the effectivity of an investment project while respecting economic risks. These are the basic elements of the thesis: analysis and effectivity performance and evaluation of economic risks of an investment project. The goal as well as the outcome of the thesis is using these principles above for conducting a case study based on a real data.
Evaluation of the Efficiency of the Investment Project Respecting Economic Risk
Keywords: Investiční projekt; hodnocení efektivnosti; analýza rizik; ekonomický ukazatel; aplikace Crystal Ball.; Investment project; effectivity performance; risk analysis; economic index; Crystal Ball method application.